2017
DOI: 10.1096/fj.201700178r
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal administration of mesenchymoangioblast‐derived mesenchymal stem cells abrogates airway fibrosis and airway hyperresponsiveness associated with chronic allergic airways disease

Abstract: Structural changes known as airway remodeling (AWR) characterize chronic/severe asthma and contribute to lung dysfunction. Thus, we assessed the efficacy of induced pluripotent stem cell and mesenchymoangioblast-derived mesenchymal stem cells (MCA-MSCs) on AWR in a murine model of chronic allergic airways disease (AAD)/asthma. Female Balb/c mice were subjected to a 9-wk model of ovalbumin (Ova)-induced chronic AAD and treated intravenously or intranasally with MCA-MSCs from weeks 9 to 11. Changes in airway inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 56 publications
(86 reference statements)
2
27
0
Order By: Relevance
“…Even epithelial repair factors that do not have any effects on chronic AAD‐induced total lung collagen concentration levels were found to modestly suppress AHR (19). Above all, we have found that therapies that target aberrant collagen levels are most effective in reducing chronic AAD‐induced AHR over other ECM proteins or AWR parameters (14, 19, 22, 23).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Even epithelial repair factors that do not have any effects on chronic AAD‐induced total lung collagen concentration levels were found to modestly suppress AHR (19). Above all, we have found that therapies that target aberrant collagen levels are most effective in reducing chronic AAD‐induced AHR over other ECM proteins or AWR parameters (14, 19, 22, 23).…”
Section: Discussionmentioning
confidence: 95%
“…Separate serial sections were immunohistochemically stained for TGF‐β1 using a pAb (sc‐146, 1:1000 dilution; Santa Cruz Biotechnology, Dallas, TX, USA); α‐smooth muscle actin (a marker of myofibroblast differentiation) using an mAb (M0851, 1:200 dilution; Agilent Technologies, Santa Clara, CA, USA); or thymic stromal lymphopoietin (TSLP) (a marker for epithelial damage) using a pAb (ABT330, 1:1000 dilution; MilliporeSigma). Morphometric analysis of all end points was performed in a blinded fashion as previously described (14, 19, 22, 23).…”
Section: Methodsmentioning
confidence: 99%
“…MB-based mesenchymal cell generation protocols, in contrast to protocols based on spontaneous hPSC differentiation, allow for standardized manufacturing of well-defined pure MSC, PC and SMC cell populations for clinical applications. The therapeutic efficacy of MB-derived MSCs has been demonstrated in animal models of hindlimb ischemia and chronic allergic airways disease [101,102]. Further animal and in vitro studies are needed to compare the therapeutic potential of MB-derived MSCs and various PC subsets, to explore whether more specific and efficient targeting of inflammation versus tissue degeneration could be achieved with these populations.…”
Section: Discussionmentioning
confidence: 99%
“…In hindlimb ischemia, intramuscular injection of MB-derived MSCs inhibited tissue damage, improved peripheral blood flow and significantly reduced toe necrosis, suggesting that these cells have a significant protective effect against ischemic insult [101]. Royce et al [102], induced chronic allergic airways disease (AAD)/asthma by administering aerosolized ovalbumin to ovalbumin-sensitized mice. After establishing chronic AAD, mice were treated with MSCs administered intravenously or intranasally.…”
Section: Mb Potential For Cellular Therapiesmentioning
confidence: 99%
“…37,38 Conversely, a study in mice with ovalbumin-induced asthma similarly demonstrated abrogation of airway injury after intranasal administration of MSCs. 39 Additionally, these investigators demonstrated that intranasal delivery was more successful in reducing lung fibrosis, inflammation, and airway reactivity than the intravenous route.…”
Section: Discussionmentioning
confidence: 99%